PENGARUH INDEKS PEMBANGUNAN MANUSIA, PERTUMBUHAN EKONOMI, DAN PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI PROVINSI KEPULAUAN RIAU TAHUN 2008-2012 - , Tia Samarta ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This Research is to analyze how influence of Human Development Index ( HDI ), economic growth and unemployment against poverty rate in Riau Islands Province. The data used in this research is panel data which is a combination of data from the regencies and cities in the Riau Islands Province by the time period 2008 to 2012. Analytical tools used in this research are multiple linear regression. The study also looked at how the condition of inequality between the regencies and cities in Riau Islands Province and see how its relationship with poverty rate. Based on the results of analysis by using multiple linear regression approach Random Effect, it was found that simultaneously the Human Development Index (HDI), economic growth and unemployment affect the poverty rate in Riau Islands Province with significant probability. Partially the increase of Human Development Index (HDI) will be able to reduce poverty rate in Riau Islands Province with significant probability. Partially the increase unemployment figures will be able to increase the poverty rate in Riau Islands Province with significant probability. Economic growth in partial did not influence significantly to poverty rate in Riau Islands Province. Based on the value of the index Williamson found that inequality between regions in the regencies and cities in the Province of Riau Islands included in the category of high inequality, as well as having a positive relationship with the poverty rate in Riau Islands Province.